Figure 6 from: Wallin H, Kvamme T, Bergsten J (2017) To be or not to be a subspecies: description of Saperda populnea lapponica ssp. n. (Coleoptera, Cerambycidae) developing in downy willow (Salix lapponum L.). ZooKeys 691: 103-148. https://doi.org/10.3897/zookeys.691.12880 - Wallin, Henrik; Kvamme, Torstein; Bergsten, Johannes (Zenodo, 2017)
Figure 6 - Habitus (dorsal view). a ♀ Saperda populnea populnea (Linnaeus, 1758), Knutby (Uppland), Sweden, 13.5 mm b ♀ S. populnea lapponica ssp. n., Ljørdalen, Norway, 12.5 mm c ♀ S. populnea lapponica ssp. n., Kiruna (Lappland), Sweden, 12,0 mm d ♂ S. populnea populnea, Uppsala (Uppland), Sweden, 11.5 mm e ♂ S. populnea lapponica ssp. n., Ljørdalen, Norway, 10.5 mm f ♂ S. populnea lapponica ssp. n., Kiruna (Lappland), Sweden, 10.0 mm. Scale bar 10 mm.